Endoplasmic Reticulum Associated Protein Degradation (ERAD) in the Pathology of Diseases Related to TGFβ Signaling Pathway: Future Therapeutic Perspectives - Gariballa, Nesrin; Ali, Bassam R. (Frontiers in Molecular Biosciences, 2020)
The transforming growth factor signaling pathway (TGF) controls a wide range of cellular activities in adulthood as well as during embryogenesis including cell growth, differentiation, apoptosis, immunological responses and other cellular functions. Therefore, germline mutations in components of the pathway have given rise to a heterogeneous spectrum of hereditary diseases with variable phenotypes associated with malformations in the cardiovascular, muscular and skeletal systems. Our extensive literature and database searches revealed 47 monogenic diseases associated with germline mutations in 24 out of 41gene variant encoding for TGF components. Most of the TGF components are membrane or secretory proteins and they are therefore expected to pass through the endoplasmic reticulum (ER), where fidelity of proteins folding is stringently monitored via the ER quality control machineries. Elucidation of the molecular mechanisms of mutant proteins’ folding and trafficking showed the implication of ER associated protein degradation (ERAD) in the pathogenesis of some of the diseases. For example, hereditary hemorrhagic telangiectasia types 1 and 2 (HHT1 & HHT2) and familial pulmonary arterial hypertension (FPAH) associated with mutations in Endoglin, ALK1 and BMPR2 components of the signaling pathway, respectively, have all exhibited loss of function phenotype as a result of ER retention of some of their disease-causing variants. In some cases, this has led to premature protein degradation through the proteasomal pathway. We anticipate that ERAD will be involved in the mechanisms of other TGF signaling components and therefore warrants further research. In this review, we highlight advances in ER quality control mechanisms and their modulation as a potential therapeutic target in general with particular focus on prospect of their implementation in the treatment of monogenic diseases associated with TGF components including HHT1, HHT2 and PAH. In particular, we emphasis the need to establish disease mechanisms and to implement such novel approaches in modulating the molecular pathway of mutant TGF components in the quest for restoring protein folding and trafficking as a therapeutic approach.